Architectural Style and Technique in Prehistoric Sistan: Sustainable Patterns in Shahr-i-Sokhta Architecture from Early 3rd Millennium to the Beginning of the 2nd Millennium BC - Moradi, Hossein (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2020)
In the 3rd millennium B.C, Shahr-i-Sokhta witnessed spatial and situational specialisation in both architectural structure and residential texture and residential buildings follow a standard plan. The general plan of these houses consists of a courtyard or a large roofless room and one or more internal smaller roofed rooms. Spatial partitioning inside this rectangular building was based on the function of each space, requirements, and taste of the inhabitants. In this paper, all the existing constructions in Shahr-i-Sokhta has been categorised as 1) normal houses, 2) special houses and 3) public buildings based on some factors like the area of the building; the composition of architectural spaces and structural units within each building; the presence of special architectural elements; and the quality of mortars being used in buildings. Normal houses are those buildings that regarding either area or functional analysis plan belonged to a family group, probably one or two cores, including a father and perhaps some children. The spaces within the structure are close to basic standard architecture and construction that are comprised of two to four living rooms and two to six storage or side rooms. Special houses are residential spaces in Shahr-i-Sokhta that although have many commonalities in plan and composition with normal houses, due to their large area can not be considered as normal houses and probably were the habitat of a multi-core family and this is why they were built considerably larger and had more living and storage rooms.